2019
DOI: 10.1039/c9nr02548k
|View full text |Cite
|
Sign up to set email alerts
|

Disorder limits the coherent phonon transport in two-dimensional phononic crystal structures

Abstract: κCNPnC showed a non-monotonic dependence on porosity, and the localization of coherent phonons induced a substantial suppression of κD-C3N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 84 publications
3
41
0
Order By: Relevance
“…The vibrational eigen-mode analysis revealed that the phonon localization and phonon back scattering around the nanopores are the major factor responsible for the ultra-low thermal conductivity of GPC. Similar results have also been reported in some other studies (Hu et al, 2019). Analogously, (Cui et al, 2018a) reported that the thermal conductivity of silicene phononic crystal is not sensitive to temperature but strongly depends on the porosity ratio, as that in 3D phononic crystal (Hopkins et al, 2011).…”
Section: From the Perspective Of Phonon-wave Picturesupporting
confidence: 89%
“…The vibrational eigen-mode analysis revealed that the phonon localization and phonon back scattering around the nanopores are the major factor responsible for the ultra-low thermal conductivity of GPC. Similar results have also been reported in some other studies (Hu et al, 2019). Analogously, (Cui et al, 2018a) reported that the thermal conductivity of silicene phononic crystal is not sensitive to temperature but strongly depends on the porosity ratio, as that in 3D phononic crystal (Hopkins et al, 2011).…”
Section: From the Perspective Of Phonon-wave Picturesupporting
confidence: 89%
“…2b). The phonon participation ratio, P , measures the spatial localization of a phonon mode, and it is defined as 45,46 where N is the total number of atoms and ε iα, is the α th cartesian component of the eigen-mode for the ith atom. P is a dimensionless quantity ranging from 1/N to 1, with ≈ 1 denoting the propagating mode and ≈ 0 denoting the localized mode.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, increasing efforts have been made to control the thermal transport [36][37][38]. Analogous to the technique of anti-reflective coating and reflective coating, we can apply the reversion between the half-wave loss and the no-wave loss for the reflected phonon to manipulate the thermal transport across an interface.…”
Section: Discussionmentioning
confidence: 99%